(untitled) (Psychology Travelogs, 2025)
The article examines the multidimensional nature of resilience as a dynamic process of adaptation, recovery, and development that emerges from the interaction of internal (psychological, personal, biological) and external (social, cultural, institutional) resources across individual, family, organizational, and societal levels. It presents leading foreign concepts (A. Masten, M. Rutter, F. Walsh, E. Morel, S. Heshmat) describing universal mechanisms of resilience, alongside Ukrainian approaches (O. Merzlyakova, L. Muzychko, O. Kredenzer, Ye. Potapchuk, O. Polishchuk) that adapt these models to Ukraine’s socio-cultural and wartime context. The analysis highlights differences in focus: foreign studies prioritize universal biopsychosocial frameworks and flexible adaptation mechanisms, whereas Ukrainian research emphasizes practical strategies for resilience in conditions of war, collective and organizational stability, and post-traumatic growth. An integrated model is proposed that combines universal principles with cultural-historical, economic, and conflict-related realities, outlining benefits for psychological assistance, community support, and professional training. The model’s multi-level structure addresses individual resource development, family cohesion, supportive organizational environments, and societal solidarity. The paper also identifies the need for empirical validation of this integrated approach among diverse target groups – students, educators, military personnel, and internally displaced persons aimed at enhancing psychological well-being and diagnostics the resilience of Ukrainian society under conditions of prolonged crisis.